THE EFFECTS OF SERVICE RECOVERY ON CONSUMER SATISFACTION BOBA DRINK XING FU TANG INDONESIA - JULIANA .; JERRY ONG; STEVEN ELROY; FRANCISCO JONATHAN (JURNAL ILMIAH KOHESI, 2021)
In recent times, service recovery is receiving important attention in the service operations management literature. Servicerecovery involves actions designed to solve problems, change negative attitudes of dissatisfied consumers and retaincustomers. The research objective was to analyze the effect of service recovery on customer satisfaction. This research is adescriptive study with a quantitative approach. The sampling method was simple random sampling. The sample size is 170people. The results show that it is true that service recovery has a considerable influence on customer satisfaction becausethe ability of service recovery explains the satisfaction of 73.3% and the most influential indicator is the way employeesbehave.